2021
DOI: 10.1029/2021jf006369
|View full text |Cite
|
Sign up to set email alerts
|

Updated Surge‐Type Glacier Inventory in the West Kunlun Mountains, Tibetan Plateau, and Implications for Glacier Change

Abstract: Glacier surging is a dynamic instability that affects the flow of some glaciers, modifying the glacier area, surface velocity, and surface elevation. It is also among the major causes of ice dams and glacier lake floods. Previous studies have shown that in the West Kunlun Mountains| (WKM) where a cluster of surge‐type glaciers had been found, the glaciers were relatively stable in recent years. Nevertheless, the surge cycle and its impact on glacier changes on a regional scale are poorly understood. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…For example, some glaciers presented short‐term (one or several years) advances within a retreating trend during 1972–2020, while some exhibited a continuous advance or continuously retreated (Guan et al., 2022). However, most glaciers (about 405, including large and small glaciers and Guliya) in the WKM had a relatively stable terminus position, with total variations of <0.12 km during 1972–2020 (Guan et al., 2022). Thus, our assumption that ice‐covered areas on Guliya did not change during 1970–2019 is reasonable.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, some glaciers presented short‐term (one or several years) advances within a retreating trend during 1972–2020, while some exhibited a continuous advance or continuously retreated (Guan et al., 2022). However, most glaciers (about 405, including large and small glaciers and Guliya) in the WKM had a relatively stable terminus position, with total variations of <0.12 km during 1972–2020 (Guan et al., 2022). Thus, our assumption that ice‐covered areas on Guliya did not change during 1970–2019 is reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…The spatial‐temporal patterns of glacier velocities in the WKM are complicated. The velocities in the centerline within the ablation zone of some glaciers were larger in summer (∼0.3 m d −1 ) compared to those in winter (<0.05 m d −1 ) during 2017–2019, while the velocities of some glaciers were faster during winter than during summer (Guan et al., 2022). For surge‐type glaciers, Yasuda and Furuya (2015) found that the surface velocity is faster in early winter than in summer because of the presence of surface meltwater that reroutes through the englacial and subglacial drainage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations